1957
DOI: 10.1042/bj0660289
|View full text |Cite
|
Sign up to set email alerts
|

The origin of melezitose: a biochemical relationship between the lime tree (Tilia spp.) and an aphis (Eucallipterus tiliae L.)

Abstract: CARBOHYDRATE METABOLISM OF SKIN 289 cluding citrate, a-oxoglutarate, succinate, fumarate and malate, only glucose, fructose, lactate and pyruvate produced maximal mitotic activity over 4 hr. in mouse-ear skin in vitro. The effects of glucose 1-phosphate are difficult to interpret without further experiments to determine the fate of the compound. Barron et al. (1948) and Griesemer & Gould (1954) found citrate to have no effect upon skin respiration. Barron et al. also failed to demonstrate i80citric dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

1959
1959
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…] is an ␣-glucose-containing trisaccharide found in honeydew and manna, which are sugar-rich liquid and solid deposits, respectively, associated with the leaves and branches of various trees and shrubs (32). Although it was initially believed that melezitose was an oligosaccharide that was naturally present in various plants (33), it was later concluded that certain insects are responsible for melezitose production, since this sugar is absent from the tree sap used by such insects to form honeydew (32).…”
Section: Melezitose [␣-D-glcp-(1¡3)-␤-d-fruf-(2¡1)-␣-d-glcpmentioning
confidence: 99%
“…] is an ␣-glucose-containing trisaccharide found in honeydew and manna, which are sugar-rich liquid and solid deposits, respectively, associated with the leaves and branches of various trees and shrubs (32). Although it was initially believed that melezitose was an oligosaccharide that was naturally present in various plants (33), it was later concluded that certain insects are responsible for melezitose production, since this sugar is absent from the tree sap used by such insects to form honeydew (32).…”
Section: Melezitose [␣-D-glcp-(1¡3)-␤-d-fruf-(2¡1)-␣-d-glcpmentioning
confidence: 99%
“…It was initially hypothesized that melezitose is an oligosaccharide that is naturally present in various plants (28). However, it was later found that certain insects are responsible for melezitose production, when they use carbohydrates present in tree sap, by itself devoid of melezitose, to form honeydew (27). In the current work, we investigated the transcriptional regulation of the gene clusters associated with the metabolism of the raffinose family sugars and melezitose.…”
mentioning
confidence: 99%
“…The raf locus in the B. breve UCC2003 genome is located adjacent to the mel gene cluster, which allows the strain to metabolize the trisaccharide melezitose [␣-D-Glcp-(1¡3)-␤-D-Fruf-(2¡1)-␣-D-Glcp], found in honeydew and manna, which are sugar-rich liquid and solid deposits, respectively, associated with leaves and branches of various trees and shrubs (20,27). It was initially hypothesized that melezitose is an oligosaccharide that is naturally present in various plants (28).…”
mentioning
confidence: 99%
“…Como já mencionado anteriormente, a ocorrência da reação de trans-D-frutosilação no mel não foi comprovada até o momento. Com relação a melezitose e a 1-cestose, alguns autores consideraram estes trissacarídeos como constituintes da seiva de várias espécies de plantas 86 enquanto, outros 21,87 têm sugerido que esses glicídios seriam carreados para colméia através de coleta das excreções adocicadas de afídeos, as quais estão presentes na superfície das plantas. De fato o mel de melato que é produzido através de excreções de afídeos é rico nesses 2 trissacarídeos enquanto, méis monoflorais têm somente quantidades ínfimas desses compostos 4 .…”
Section: Origemunclassified
“…De fato o mel de melato que é produzido através de excreções de afídeos é rico nesses 2 trissacarídeos enquanto, méis monoflorais têm somente quantidades ínfimas desses compostos 4 . Outros autores 86 também sugeriram que a presença de erlose poderia ser devida a ação de afídeos, porém, a erlose é encontrada em bem maior quantidade que a melezitose em méis monoflorais. Portanto, a origem da erlose estaria principalmente associada à reação de trans-D-glicosilação no mel.…”
Section: Origemunclassified